VOLCANOSTRATIGRAPHY AND PETROGENESIS OF MOUNT BALURAN, SITUBONDO REGENCY, EAST JAVA - Fadhly Rizki Yazid, Moh
Mount Baluran is located in Baluran National Park, Situbondo Regency, East Java. Geological mapping of Mount Baluran has been carried out using lithostratigraphic principles in previous studies. In addition, specific petrogenesis studies are still minimally carried out in the caldera of Mount Baluran. Therefore, this study aims to make a geological map of Mount Baluran using volcanostratigraphic principles and conduct specific petrogenesis studies based on the evolution of Mount Baluran's magma. This research was conducted using field mapping method with a research area of 52 km2 . Based on the mapping results, data was obtained which was 101 outcrops. A total of 26 rock samples were made into thin sections for petrographic analysis. A total of 4 samples were carried out XRF and ICP-MS analysis for geochemical analysis. The results of petrographic and geochemical analysis will be used in petrogenesis analysis. The study area consists of 9 geomorphological units. These geomorphological units are combined with field data to produce volcanostratigraphy. Volcanostratigraphy of the study area consists of 1 khuluk (Khuluk Baluran), 3 gumuk (Gumuk Baluran, Gumuk Kacip, and Gumuk Klosot), and 14 rock units. The materials identified in the study area are lava and pyroclastic breccia. The material is produced from 3 phases, namely the Baluran Phase, the Kacip Phase, and the Klosot Phase. The primary geological structures identified in the study area are vesicular, sheeting joint, and columnar joint. The secondary geological structures identified in the study area is fault. The evolution of magma from Mount Baluran is reflected in the microtexture analysis of plagioclase, anortite composition in plagioclase, CIPW analysis, and Harker diagram. The evolution of Mount Baluran magma involves adiabatic decompression, fractional crystallization, self convection mixing, primitive magma injection, and cooling. The magma affinity and tectonic setting of Mount Baluran are determined by discriminant diagrams. The results of the analysis showed Mount Baluran has calc-alkaline affinity magma with tectonic setting in the island arc